Numeric-experimental analysis of the impact in panels of aluminium - Elza Marisa P. de F. Chagas (2009)
In this paper, an attempt is made to evaluate reliability of failure critical structural elements subjected to loading conditions characteristic for power equipment. An estimated lifetime is one of the most important parameters defining equipment reliability. The paper shows complexity of the lifetime evaluation in such conditions. Practical solutions made in the investigation are based on the experimental data, obtained in low-cycle fatigue strength and fracture mechanics tests. The lifetime is considered both at the stage of crack initiation and at the stage of crack propagation. Safety factors related to both of these stages are investigated and recommendations related to lifetime calculation are formulated.